Advertisement call of the rare, explosive breeding caatinga horned frog Ceratophrys joazeirensis Mercadal de Barrio, 1986 (Anura, Ceratophryidae) - Zaidan, Bárbara Fernandes; Leite, Felipe Sá Fortes (Zootaxa, 2012)
The present study describes for the first time the advertisement call of Ceratophrys joazeirensis Mercadal de Barrio, 1986. This rare explosive breeding species is endemic to the semi-arid Caatinga biome and is known only from four localities in northeastern Brazil: Municipality of Juazeiro, State of Bahia (type locality); Municipalities of Araruna and Triunfo, State of Paraíba; and Municipality of Passa and Fica, State of Rio Grande do Norte (Mercadal de Barrio, 1986; Vieira et al. 2006; Santos et al. 2009).